Video podcast as alternative education media of Borobudur temple campaign during pandemic COVID-19 - Bambang Kasatriyanto; Arif Ardy Wibowo; Roziani Mat Nashir (International Journal of Communication and Society, 2021)
COVID-19 pandemic changes all aspects of human life. Various adaptations need to be carried out by the community, and communication must be adaptive in making these adjustments. The use of Borobudur Temple, either in tourism or education, was also affected by this pandemic. The Borobudur Conservation Center, as one of the managers of Borobudur Temple, initiated a new way of publishing and educating the public. Through the YouTube video podcast BUSUR, the Borobudur Conservation Center tries to take advantage of the new publication model as an effort to keep educating the public about Borobudur Temple. This analysis aims to determine how the public responds to alternative media called BUSUR video podcast made by the Borobudur Conservation Center. Community response is measured based on the number of subscribers and views count on BUSUR video content uploaded. Based on the data obtained, data will describe it using a qualitative descriptive approach. The research includes collecting various data from relevant sources. Data collection was carried out through observation. Then select and analyze data. Then end by making conclusions from the results obtained. Based on this study, the results obtained shows that the BUSUR podcast's video content received an excellent public response. By the data, there is an addition of 2490 subscribers and 35,000 video podcast screenings throughout 2020. Based on this analysis, the BUSUR video podcast as an alternative media to introduce Borobudur Temple to the public is very successful because the theme of cultural heritage still gets quite a lot of attention from the crowd.